2000
DOI: 10.1046/j.1523-1755.2000.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between methylmalonic acid and cobalamin in uremia

Abstract: We demonstrated a within-patient inverse relationship between the concentrations of methylmalonic acid and cobalamin in plasma from these uremic patients. Despite the fact that only two of the patients developed subnormal plasma cobalamin values, we demonstrated a B12 depletion during the withdrawal period. Treatment with cyanocobalamin tablets once daily was found efficient, but the oral doses should possibly be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In our investigation, we found a distinctly increased HCY level in patients with hemodialysis (41). A major reason for the high prevalence of hyperhomocysteinemia in dialysis patients is the strongly disturbed renal remethylation of HCY to methionine which is only partly reversible by vitamin supplementation (42,43). A major reason for the high prevalence of hyperhomocysteinemia in dialysis patients is the strongly disturbed renal remethylation of HCY to methionine which is only partly reversible by vitamin supplementation (42,43).…”
Section: Hyperhomocysteinemia In Renal Patientssupporting
confidence: 46%
“…In our investigation, we found a distinctly increased HCY level in patients with hemodialysis (41). A major reason for the high prevalence of hyperhomocysteinemia in dialysis patients is the strongly disturbed renal remethylation of HCY to methionine which is only partly reversible by vitamin supplementation (42,43). A major reason for the high prevalence of hyperhomocysteinemia in dialysis patients is the strongly disturbed renal remethylation of HCY to methionine which is only partly reversible by vitamin supplementation (42,43).…”
Section: Hyperhomocysteinemia In Renal Patientssupporting
confidence: 46%
“…Therefore, a substantial proportion of the high MMA concentrations in the present study are unlikely to be attributable to impaired kidney function, and are thus more likely to be due to poor vitamin B 12 status. An MMA elevation above 0.70 mmol=l is unlikely to be explained by moderately impaired renal function alone (Rasmussen et al, 1990a,b;Moelby et al, 2000). More work is clearly needed to establish reasonable MMA reference limits in older people with partially impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent publication by Moelby et al showed the relationship between MMA level and vitamin B 12 concentration in patients on chronic hemodialysis treated with intramuscular cobalamin injections (1mg every third month) (40). Using within-patient comparisons, the authors found that even if MMA levels were high, the patients responded quickly to changes in vitamin B 12 concentrations.…”
Section: Discussionmentioning
confidence: 99%